Physically Based Collaborative Simulations under Ring-Like Network Configurations - Joono Cheong; Jongwoo Park; Niculescu, S.-I. (IEEE Computer Graphics and Applications, 2009)
A state-synchronization method for physically based simulations provides equivalent visual scenes at remote sites on ring-like networks. The simulation runs independently on each participating site so that sites can immediately process and display any local user's action, allowing high responsiveness.